Pemahaman Karisma dan Kepemimpinan dalam Konteks Manajemen Pendidikan: Tinjauan Berdasarkan Teori Max Weber - Rahmalina Rahmalina; Silfia Hanani; Aisyah Syafitri; Muaddyl Akhyar; Dilla Gusti Elfira (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Max Weber's theory-based leadership emphasises the importance of authority, especially charismatic authority, in influencing and motivating others. Charisma, as a key characteristic, plays a central role in helping educational leaders to achieve their vision and overcome various obstacles. Through a deeper understanding of these concepts, educational leaders can be more effective in creating an inclusive and social justice-orientated educational environment. The purpose of this study is to explain the understanding of charisma and leadership in the context of education management: A Review Based on Max Weber's Theory. The method used in this study uses qualitative research procedures using a research approach in the form of a literature study. The sources of information in this study are reviewed from various novel sources of literature, research reports, scientific essays, theses, dissertations and posts both print and electronic related to Understanding Charisma and Leadership in the Context of Education Management: A Review Based on Max Weber's Theory. The results of this study show that educational leaders have a key role in shaping a more inclusive and socially just future for education. With characteristics of charisma, strong leadership and commitment to social justice values, educational leaders can help create equitable learning environments, provide every student with equal opportunities to grow and develop, and drive positive change in the education system. With charismatic and committed leaders, education has the potential to be a powerful tool in creating a more inclusive and socially just society.